Prototipe Knowledge Sharing System Kerajinan Tangan Berbasis Android - Debby Ummul Hidayah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In the organization of NA Branch of Rabak or PCNA Rabak, the issue of sharing knowledge is one that can be said to have a high enough urgency. This is evident from the lack of organizational members to share knowledge. As in the case of handicraft training, there is no regular documentation or no modules or tutorials to assist in the sharing of craft knowledge. This is what makes researchers interested in creating innovations by designing and building a prototype knowledge sharing system based on an android application about handicrafts. The system development method used in this research is the knowledge management system life cycle method or abbreviated as KMSLC which consists of an evaluate existing infrastructure process, form the KM team, knowledge capture, design KM blueprint, verify and validate the KM system, and implement the KM system. The result of this research is that an android-based knowledge sharing system prototype has been successfully designed and built to facilitate the process of sharing handicrafts, documenting the results of handicraft practices, and assisting in the process of making handicrafts.